2002
DOI: 10.1590/s0100-879x2002000300012
|View full text |Cite
|
Sign up to set email alerts
|

Low pH and calcium effects on net Na+ and K+ fluxes in two catfish species from the Amazon River (Corydoras: Callichthyidae)

Abstract: The present study analyzes Na + and K + disturbances caused by low pH in two catfish species from the Amazon River. Corydoras adolfoi inhabits ion-poor, black-stained, low pH (3.5-4.0) waters, while C. schwartzi is native to ion-rich waters at circumneutral pH. Fish were exposed to pH 3.5 Ca 2+ -free, and Ca 2+ -enriched (~500 µmol/l) water to determine the protective effects of calcium. Net Na + and K + fluxes were measured in the water collected from the fish experimental chambers. C. adolfoi was unable to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Three main water types occur in the Amazon: white (muddy) water (pH 6.2–7.2), black water (pH 3.8–4.9) and clear water (pH 4.5–7.8). Seasonal and daily variations in water pH levels are an important environmental factor affecting ion homeostasis in fish of the Amazon (Matsuo & Val 2002). Extreme water pH represents a challenge for many fish species and can limit their growth (Aride, Roubach & Val 2004), which is relevant to local producers.…”
Section: Introductionmentioning
confidence: 99%
“…Three main water types occur in the Amazon: white (muddy) water (pH 6.2–7.2), black water (pH 3.8–4.9) and clear water (pH 4.5–7.8). Seasonal and daily variations in water pH levels are an important environmental factor affecting ion homeostasis in fish of the Amazon (Matsuo & Val 2002). Extreme water pH represents a challenge for many fish species and can limit their growth (Aride, Roubach & Val 2004), which is relevant to local producers.…”
Section: Introductionmentioning
confidence: 99%
“…A similar protective effect of elevated [Ca 2+ ] e has been demonstrated for larval Rana pipens where Na + efflux rates were suppressed almost completely (87%) following acute exposure to high Ca 2+ , low pH water (Freda and Dunson, 1984). Likewise, studies of acid tolerant fish have shown that in most cases, the presence of elevated [Ca 2+ ] e levels reduces Na + efflux rates in waters of low pH, resulting in substantially reduced mortality rates (Glynn et al, 1992; Gonzalez and Dunson, 1989a; Gonzalez et al, 1998; Matsuo and Val, 2002; McWilliams, 1983; see also review by Walker et al, 1988), suggesting that tolerance of low pH environments is at least somewhat calcium-dependent. However, an understanding of the mechanistic basis by which [Ca 2+ ] e allows acid-tolerant species overcome the physical challenges imposed by low pH environs is lacking.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the DOC found in Negro habitats may have unique chelating properties utilized by native fishes to minimize ion loss [78,79], and attempts to recreate this with other DOC sources (including Sigma humic acid) have produced mixed results [26,80,81]. The latter observation may partially explain why several Negro fishes tested in native water have shown lower dependency on external Ca 2+ to charge paracellular junctions [82,83].…”
Section: Discussionmentioning
confidence: 99%